The Role of Vocational Education in Developing Students' Entrepreneurial Spirit in The Field of Economics - Muhammad Harpis; Fristya Sugesty (PT. Mifandi Mandiri Digital, 2025)
This study aims to analyze the role of vocational education in fostering students' entrepreneurial spirit in the economics field. The problem in this study is the persistently low interest and readiness of students to become entrepreneurs despite having received entrepreneurship education at university. The study used a quantitative approach with a survey method of 80 economics students who had taken vocational learning and entrepreneurship courses. Data collection was conducted through a questionnaire using a Likert scale, while data analysis used simple linear regression with the assistance of SPSS. The results showed that vocational education has a positive and significant effect on students' entrepreneurial spirit. This is evidenced by the t-test results, which obtained a calculated t-value of 8.742, greater than the t-table of 1.984, with a significance value of 0.000 <0.05. Furthermore, the coefficient of determination (R²) of 0.624 indicates that vocational education contributed 62.4% to the increase in students' entrepreneurial spirit, with the remainder influenced by other factors outside the study. Research findings indicate that practice-based learning, internships, and entrepreneurship training can increase students' creativity, self-confidence, and courage in starting a business.